INTERACTIVE EFFECT OF CAGE DENSITY AND DIETARY BLACK CUMIN LEVEL ON PRODUCTIVE EFFICIENCY IN BROILER CHICKENS - Mahfudz, L. D.; Nurfaizin, N.; Atmomarsono, U.; Suthama, N. (Diponegoro University, 2015)
The present research was aimed to evaluate an interactive effect of cage density and level ofdietary black cumin (BC) on productive efficiency of broiler chickens. A total of 270 broiler chickens(initial body weight of 163.12 ± 8.10g) were allocated into a completely randomized design with a 3 x 3factorial pattern. The first factor was the cage density (bird/m2) namely, D1 = 8; D2 = 10, and D3 = 12.The second factor was BC level (%), namely, B1 = 1; B2 = 2, and B3 = 3. Feed consumption, bodyweight gain (BWG), feed conversion ratio (FCR), protein digestibility, and income over feed cost(IOFC) were the parameters measured. Data were subjected to ANOVA and continued to Duncan test.No interaction between cage density and black cumin on all parameters was observed. Feedconsumption and FCR were increased, but BWG was lowered significantly (P<0.05) due to the cagedensities of 10 and 12 birds/m2 on weeks 2 and 3. Protein digestibility was significantly increased byfeeding 2 and 3% BC. IOFC decreased significantly (P<0.05) when cage densities were 10 and 12birds/m2. In conclusion, the improvement of productive efficiency of broiler chicken reared at the cagedensity of 12 birds /m2 can be sufficiently achieved by feeding 1% black cumin.